A tunable, power efficient active inductor-based 20 Gb/s CTLE in SerDes for 5G applications. (January 2020) - Thulasiraman, Deepanraj; Gaggatur, Javed S.
Abstract: A low-power receiver front end (RFE) with 2-tap continuous time linear equalization (CTLE) was designed in 28 nm CMOS technology. The CTLE uses a transconductance-based active inductor for high frequency operation and for area reduction. The active inductor can be tuned around 10 GHz while consuming 7.57 mW from 0.9 V power supply. The CTLE compensates about 7 dB of attenuation due to the channel at a data rate of 20 Gb/s per link, with a power efficiency of 12.6 fJ/bit/dB, nearly 4X better power efficiency than the previous works reported in the literature. It shows prominence in the receivers used for wireline I/O interfaces like USB 3.2 and PCI Express 4.0 for various 5G applications. Graphical abstract: Image 1